Does Internet Information Enhance the Intention to Switch? Evidence Shifting to Eco-Friendly Products - Angga Pandu Wijaya; Widya Prananta; Bogy Febriatmoko (Jurnal Organisasi dan Manajemen, 2023)
Purpose – The research aims to explore the impact of user experience and satisfaction on switching intentions, addressing the challenge of user retention amid growing competition. Despite this, a gap exists in understanding the role of internet information, necessitating further investigation.  Methodology – The study utilizes a quantitative, causal research approach with a questionnaire survey involving 151 respondents selected through purposive sampling. Structural Equation Modeling (SEM) is employed for data analysis. Findings – The study reveals that positive user experience encourages product switching, while user satisfaction has a negative effect with the intention to switch. Additionally, internet information moderates the impact of user satisfaction, offering insights into users' product-switching tendencies. Satisfied users are more likely to exhibit loyalty. Originality – The research explores the environmentally aware younger generation's reliance on the internet for information exchange and presents results on consumer behavior with alternative eco-friendly products.